Evaluasi Tingkat Pelayanan Pada Persimpangan Jalan Sisimangaraja Jalan-Alfalah Simpang Bersinyal - Marwan Lubis; Hamidun Batubara; Deni Maulana (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Intersections are the most important factor in determining the capacity and travel time on a road section. The development of transportation in the city of Medan has had an impact on increasing the movement of people, goods and services. This also greatly demands increased transportation facilities and infrastructure in the city of Medan. The increase in the number of vehicles that is not balanced with infrastructure will cause conflicts on roads, especially at the intersection of three Jalan-Sisingamangaraja Jalan .Alfalah To anticipate This requires further study or research. In this research, analysis of intersection performance calculations uses the 1997 (MKJI) guidelines. The survey was carried out on Monday 14 August 2023 to 20 August 2023. Then the peak hours were searched for the volume of vehicle flow crossing the three intersections. Then create a new cycle time for the intersection. The results of the analysis in this research, from survey results, by looking for new cycle times to reduce queue lengths and delays (Delay). The new cycle time obtained to reduce queue lengths and delays for the three intersections on the northern approach is 859.927 seconds/intersection. Then at the southern approach with a total delay of 2,056,013 sec/intersection and at the western approach with a delay of 307,555 sec/intersection. For existing conditions the queue length (QL) is 1321 meters for the northern approach, (QL) 1372 meters for the southern approach and (QL) 1321 meters for the west